Optimal Capital Structure and Risk Management Policies of Banks That Use CoCo Futures to Hedge Financial-Sector Risk - Goldstein, Robert S; Yang, Fan (Review of Finance, 2024)
Abstract We investigate the joint optimal risk management and capital structure decisions of banks when they use contingent-convertible (CoCo) futures contracts to hedge financial-sector risk. In spite of banks choosing significantly higher leverage ratios, their default probabilities drop appreciably while their equity values increase, allowing banks to compete more favorably with the shadow-banking system. Banks’ value-maximizing decision to hedge financial-sector risk unintentionally leads to an economy with extremely low aggregate bank default rates across all future states of nature. Thus, CoCo futures offer a powerful microprudential and macroprudential policy tool. That banks choose not to hedge financial-sector risk in practice is consistent with managers internalizing bank bailouts.